CONCEPT OF POET IN SANSKRIT POETICS: FORM AND ANALYSIS (WITH SPECIAL REFERENCE TO NATYASHASTRA AND ABHINAV BHARATI) - Jain, Sumedha; Sharma, Yogesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In Sanskrit poetics, the concept of poet is a subject of deep and wide consideration. A poet is rich in creative talent who expresses society, nature and human emotions through poetry. In Sanskrit poetics, the poet has been called "Kavyasya Karta" (composer of poetry). “Lokottaravarnananipunakavikarma kavyam” means the work of a poet skilled in describing the world is poetry. The duty of a poet is not only to compose poetry, but he is a multifaceted personality of the society, who encompasses creation, knowledge and society together. The concept of poet in Sanskrit poetics is a deep and multidimensional subject, which has been defined in detail by the ancient scholars in their texts. A poet is one who is adept in the art of expressing emotions and can reach the depth of meaning through words. The concept of poet in Sanskrit poetics has not been limited to just a verse-maker, but it emerges as a visionary who coordinates creativity, classical knowledge and spiritual wisdom and whose main objective is to create such literature that uplifts the society through education, entertainment (Vinod) and Rasanubhuti. Therefore, the poet is not only a creator of artistic works, but also a moral and spiritual guide. His responsibility is to maintain and propagate social values, as well as challenge the norms and inspire change. He confronts contemporary issues while building a bridge between tradition and modernity and maintaining cultural heritage. In Sanskrit, the word 'poet' is derived from the root 'ku', which means 'to see' or 'to create'. Hence, the literal meaning of 'poet' is 'seer' or 'creator'. The derivation and definition of the word 'poet' has been elaborated in various texts and scriptures of Sanskrit. According to Kavyamimamsa, the meaning of poet is - one who describes. According to Mammata, the work of a poet who is skilled in describing the supernatural is called 'poetry'. Hence, skill in description is considered to be the main duty of a poet. The work of a poet has been given the title of the world of poetry and the poet has been considered to be the creator of the world of poetry. The world of poetry which the poet creates is his own imagined world. Acharyas like Bharatmuni and Abhinavgupta have presented deep contemplation on the process of creation of this imagined world of the poet and its qualities in Natyashastra and Abhinavbharati respectively. Apare kavyasansare kavirekah prajapatih. The world changes as it is.